Effects of Alcohol towards Quality of Life in the Indigenous Groups of the West Coast Division, Sabah, Malaysia - Asong Joseph; Helen Benedict Lasimbang; Sandi James; Chua Bee Seok (2020)
Alcohol consumption has consequences for the health and quality of life of individuals and communities. It is a problem among some of the Indigenous groups of Sabah and Sarawak with some of the highest prevalence of risky drinking in Malaysia. Alcohol is considered to be part of the culture of some of these Indigenous groups and a way to maintain the connection to their culture and traditions. However, drinking too much on a single occasion and drinking regularly over time is not a part of the culture. Therefore, this study aimed to investigate the positive and negative effects of alcohol on quality of life (QoL) of an Indigenous community of Sabah. A total of 56 villagers from the West Coast Division of Sabah were interviewed in focus group discussions using the diamond dialogue tool. Data were analysed using thematic analysis and revealed that alcohol consumption has both beneficial and adverse effects on health, behavioural, social, economic and psychological factors, depending on the drinking patterns. These harmful results suggest that awareness and harm-reduction programmes may help to empower the Indigenous groups of Sabah to reduce alcohol-related harm.